(untitled) (Itinera, 2025)
Roots, body, listening. Art as a practice for sensing biodiversity. Conversation with Laura Pitingaro In this dialogue with artist Laura Pitingaro – currently based in Palermo, where she carries out a research practice at the intersection of visual arts and ecology – the deep roots of an artistic approach emerge that weaves together bodily sensitivity, spiritual tension, and attentiveness to the living world. Trained in painting at the Academy of Fine Arts in Verona and further refined through experiences at the Fondazione Ratti with Anish Kapoor and Karel Appel, Pitingaro retraces the key stages of her development, from early explorations in drawing to her most recent site-specific installations and sensory performances. The interview investigates the role of imagination, sensory memory, and the body as instruments of knowledge and relation to the environment. Art is here conceived as a form of listening and care, capable of giving voice to biodiversity beyond scientific language. Reflecting on the transformative power of aesthetic experience, the artist invites us to rediscover a deeper connection between humans and other forms of life.